2018
DOI: 10.4314/ahs.v18i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Audit of insulin prescription patterns and associated burden among diabetics in a tertiary health institution in Nigeria

Abstract: BackgroundInsulin is one of the most important anti-diabetic agents in the management of diabetes even among type 2 diabetic.ObjectiveThere was need to assess insulin adherence, mode of insulin delivery and burden of insulin usage among diabetics.MethodsA cross-sectional, prospective questionnaire, orally administered at a Diabetes Clinic of a University Teaching Hospital, SouthWest, Nigeria. Participants were consecutive patients with diabetes who were 18 years or older presently on insulin either alone or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
2
16
1
1
Order By: Relevance
“…Olamoyegun et al in Nigeria, found around 90% of insulin users were taking ≤40 insulin units/day. 13 The frequency of subjects taking a fewer number of injections (1 or 2) per day was higher, and the frequency of the subjects having at least four injections/day was lower, in this study than observed in the Indian-and the Worldwide-ITQ studies. These reflect greater use of premixed insulins and lesser use of basal-bolus insulin regimen by the subjects of the current study in comparison to those studies.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Olamoyegun et al in Nigeria, found around 90% of insulin users were taking ≤40 insulin units/day. 13 The frequency of subjects taking a fewer number of injections (1 or 2) per day was higher, and the frequency of the subjects having at least four injections/day was lower, in this study than observed in the Indian-and the Worldwide-ITQ studies. These reflect greater use of premixed insulins and lesser use of basal-bolus insulin regimen by the subjects of the current study in comparison to those studies.…”
Section: Discussioncontrasting
confidence: 58%
“…7 Many guidelines have been published for ideal insulin injection practice, 2,8 but unfortunately, there is a large gap between the guideline recommendations and actual practice of insulin use throughout the world. [9][10][11][12][13] Data from Bangladesh specifically are scarce in this aspect.…”
mentioning
confidence: 99%
“…The characteristics of the included studies are presented in Table 1. Most (n = 19) studies were conducted in Ethiopia 12,15-32 , followed by India (n= 5) [33][34][35][36][37] , Nigeria (n= 4) [38][39][40][41] , Palestine (n= 3) [42][43][44] , one each in Cambodia 45 , Cameroon 46 , Egypt 47 , Indonesia 48 , Jordan 49 , Malaysia 50 , Pakistan 51 , Philippines 52 , South Africa 53 , Tanzania 54 , Uganda 55 , and one in Nigeria and Ghana 56 . The sample sizes in the included studies ranged from 64 to 773, and the total sample size included for this review was 12,606 (Table 1).…”
Section: Literature Search Characteristics and Quality Of Included mentioning
confidence: 99%
“…All studies were conducted in a hospital and primary healthcare setting and only three of the studies were community-based. The majority of the studies (n= 28) were carried-out among individuals with type 2 diabetes 16,[19][20][21]24,26,28,[30][31][32]34,35,[37][38][39]41,43,44,[46][47][48]50,51,53,54,56 , four studies were conducted in individuals with both type 1 and type 2 diabetes 15,17,23,40 and the remaining 11 studies simply reported diabetes 12,18,22,25,27,33,36,45,49,52,55 .…”
Section: Literature Search Characteristics and Quality Of Included mentioning
confidence: 99%
“…Nigerian workers, on the other hand, report on an audit of prescription patterns among diabetes mellitus patients in a tertiary institution 2. Liu and colleagues report on insulin resistance and diabetes mellitus3, while Ab El-Kader and others have a treatise on weight reduction on insulin resistance and adipokines regulation among obese diabetes mellitus patients 4…”
mentioning
confidence: 99%